STRATEGY FOR THE DEVELOPMENT OF THE TOURISM SECTOR OF KARANG ASRI BEACH, KENDAL REGENCY, CENTRAL JAVA THROUGH THE PLANTING OF KETAPANG TREES - Prihatiningsih, Nadya; Amalia, Zakiyatul; Pratama, Muhammad Abduh; Kusumawati, Diah; Sufa, Faela (Indonesian Journal of Devotion and Empowerment, 2021)
Karang Asri Beach is a beach tour that should attract a lot of tourists to come. But the potential of the beach is not balanced with adequate beach conditions, instead, some various shortcomings or problems include the cleanliness of the beach that is not optimally managed and the condition of the beach is hot and arid. Efforts to overcome these problems are to carry out garbage clean-up activities and tree planting around the beach. This activity aims to conduct community service so that the community is aware of the importance of cleanliness and greening of the beach to develop tourism in Kendal. Clean-up activities and greening of this beach in the form of cleaning garbage and planting 40 Ketapang Trees. This activity was held on Sunday, September 5, 2021, which was attended by the Secretary of Karangmalang Wetan Village, pokdarwis and service. This activity is carried out using practical methods directly including (1) planning activities, (2) preparation of activities and (3) planting continued with beach cleaning. The results achieved in this activity are the reduced amount of garbage around the beach and the availability of Ketapang trees that serve to prevent winds that are too strong during storms, prevent the effects of waves that abrasive the beach, as a tsunami-holding wall and can improve the coastal tourism sector. To develop Kendal tourism, it is expected that similar activities are needed sustainably to create a shady, beautiful, clean and beautiful beach atmosphere that can support the comfort of tourists. Pantai Karang Asri merupakan wisata pantai yang seharusnya banyak menarik minat wisatawan untuk datang. Namun potensi pantai tersebut tidak diimbangi dengan keadaan pantai yang memadai, sebaliknya justru ditemui berbagai kekurangan atau permasalahan yang meliputi kebersihan pantai yang kurang dikelola secara optimal serta keadaan pantai yang panas dan gersang. Upaya untuk mengatasi permasalahan tersebut adalah dengan melakukan kegiatan bersih-bersih sampah dan penanaman pohon di sekitar pantai. Kegiatan ini bertujuan untuk melakukan pengabdian masyarakat supaya masyarakat sadar akan pentingnya kebersihan dan penghijauan pantai untuk mengembangkan pariwisata yang ada di Kendal. Kegiatan bersih-bersih dan penghijauan pantai ini berupa membersihkan sampah dan menanam 40 Pohon Ketapang. Kegiatan ini dilaksanakan pada hari Minggu, 5 September 2021 yang diikuti oleh Sekretaris Desa Karangmalang Wetan, pokdarwis dan pengabdi. Kegiatan ini dilakukan menggunakan metode praktik secara langsung meliputi (1) perencanaan kegiatan, (2) persiapan kegiatan dan (3) penanaman dilanjutkan dengan bersih-bersih pantai. Hasil yang dicapai dalam kegiatan ini adalah berkurangnya jumlah sampah di sekitar pantai serta tersedianya pohon Ketapang yang berfungsi untuk mencegah angin yang terlalu kuat saat badai, mencegah efek gelombang yang mengabrasi bibir pantai, sebagai tembok penahan tsunami dan dapat meningkatkan sektor wisata pantai. Dalam upaya pengembangan pariwisata Kendal diharapkan perlu diadakan kegiatan serupa secara berkelanjutan agar menciptakan suasana pantai yang rindang, asri, bersih dan indah yang dapat menunjang kenyamanan wisatawan.